Prevalence of dermatological self‐treatment among medical doctors of a Spanish hospital - Diego Soto‐García; Ana Batalla; Sara Braña‐Valige; Sara Varela‐Fontán; Lucía Vilanova‐Trillo; Carmen Couselo‐Rodríguez; Sandra Martínez‐Fernández; Raúl Gutierrez‐Meré; Ángeles Flórez (Wiley, 2024)
Abstract Background Self‐medication is a fairly common practice among medical doctors. Although frequently seen in clinical practice, there are few published studies that describe the process of self‐treatment in dermatology, being even lower in number those that evaluate this circumstance among health professionals. Objectives To know the prevalence of self‐medication among medical professionals in our centre, to assess the need for preventive and training actions that help to avoid the misuse of dermatological treatments. Methods Descriptive cross‐sectional study based on the responses of non‐dermatologist medical professionals at the University Hospital of Pontevedra (Spain). Data were collected through a self‐administered, anonymous and voluntary online questionnaire. Results The questionnaire was completed by 283 physicians (50.63% participation rate, 62.90% females). Up to 77.39% of the physicians carried out self‐treatment for any pathology, and 55.12% for dermatological problems. The mean age of the doctors who practiced self‐treatment was significantly higher. The most used drugs were corticosteroids as topical treatment and antihistamines as systemic therapy. Irritant or allergic contact dermatitis was the most frequent pathology considered suitable for self‐medication (18.02%), followed by fungal infections (16.86%). After self‐treatment, the 7.5% needed to be seen by a dermatologist. A large group of 69.23% stated that they would recommend the treatment carried out to someone suffering from a similar process. Conclusions The prevalence of self‐treatment for skin diseases among doctors was strikingly high (55.12%). More than two‐thirds of the surveyed physicians would recommend self‐treatment in the dermatology field. As the literature on this topic is yet scarce, further studies are required to corroborate data collected in this study.